Basal cell carcinoma of the vulva: treatment with Mohs micrographic surgery. (7th January 2019) - Sinha, K.; Abdul‐Wahab, A.; Calonje, E.; Craythorne, E.; Lewis, F. M.
Summary: Vulval basal cell carcinomas (BCCs) are rare, representing < 5% of vulval malignancies and 1% of all BCCs. They often present with nonspecific symptoms and features that lead to large, poorly circumscribed and late‐presenting lesions. Current and conventional treatments used to treat vulval BCC include cryotherapy, imiquimod and excision. However, recurrence rates as high as 20% have been reported with these treatments. Furthermore, there are no current clinical guidelines for their management. We present the first reported series of patients with vulval BCC treated with Mohs micrographic surgery (MMS). We report seven cases of vulval BCC treated with MMS at a tertiary referral centre over 3 years. Follow‐up was performed at 3 months and up to 3 years. Our series demonstrates that there were no postoperative complications, functional sequelae or recurrences up to the 3‐year follow‐up. We therefore recommend that MMS should be considered in the management of vulval BCCs.